Anisotropic magnetic properties of excitons in GaAs multiple quantum wells. (January 2020) - Haldar, S.; Banerjee, A.; Kumar, Kranti; Kumar, R.; Vashisht, Geetanjali; Sharma, T.K.; Dixit, V.K.
Abstract: Anisotropic magnetic-behavior of charge carriers in a GaAs/AlGaAs quantum well is experimentally investigated under a magnetic field, perpendicular and parallel to the quantum well plane. A van-Vleck type paramagnetism is observed in the measured magnetic-susceptibility under a very-low magnetic field regime ( B < 0 . 1 T). However, with an increasing magnetic field, diamagnetic-contribution dominates over the paramagnetic counterpart and carriers in the quantum well exhibit a net-diamagnetic behavior. The magnetic-susceptibility of carriers at 2 and 300 K under a perpendicular magnetic field configuration is also explained by considering Coulomb interaction in a variational approach. On the contrary, paramagnetic and diamagnetic-susceptibility of carriers are found to be suppressed under a magnetic field that is parallel to the quantum well plane. The suppression of magnetic-properties under the latter configuration is realized by the coupling of diamagnetic energy with the quantum confinement energy due to barrier layers. Results obtained in the present study would be beneficial in controlling the magnetic-behavior of charge carriers; especially, when the magnetic contributions determine the spin/charge transport efficiency in advanced optoelectronic devices. Highlights: Anisotropic magnetic property of excitons in GaAs QW is experimentally investigated. Magnetic behavior of exciton becomes feeble under a magnetic field along QW plane. Experimentally estimated magnetic-susceptibility of QWs is theoretically explained. Role of quantum confinement on the magnetic-susceptibility of carriers is understood. Magnetic moment of exciton is controlled by a magnetic field in different directions.